An Integrated Framework for Diffusion of e-SCM by SMES in Sub-Saharan Africa - Musa, Ahmed Muhammed; Iddris, Faisal (Archives of Business Research, 2016)
The purpose of this study is to examine factors affecting electronic supply chain management (e-SCM) adoption and diffusion by Small and Medium Enterprises (SMEs) and to propose an integrative framework for successful management of e-SCM by SMEs in Sub-Saharan Africa. In this study we review existing literature and make some propositions for future empirical research. Building on existing framework this study integrates innovation diffusion theory, upper echelon theory, technology, organisation, environmental model and institutional theory and propose an integrated framework for e-SCM adoption and diffusion. The paper presents a contribution in the field of e-SCM, especially for SMEs in Sub-Saharan Africa.